2001
DOI: 10.4269/ajtmh.2001.65.346
|View full text |Cite
|
Sign up to set email alerts
|

The value of an immunoenzymatic test (enzyme-linked immunosorbent assay) for the diagnosis of strongyloidiasis in patients immunosuppressed by hematologic malignancies.

Abstract: Abstract. The diagnosis of strongyloidiasis relies upon the identification of the parasite in stool samples. In 1981, a serologic assay was developed, which was useful in the diagnosis of strongyloidiasis in the immunocompetent host. In the present study, we evaluated the enzyme-linked immunosorbent assay (ELISA) in patients with hematologic malignancies. Between April 1995 and December 1998, sera from 164 consecutive patients were tested for the presence of IgG antibody to Strongyloides stercoralis. Patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
64
1
8

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(83 citation statements)
references
References 28 publications
(42 reference statements)
6
64
1
8
Order By: Relevance
“…5 None of our patients enrolled in the prospective study, including those who subsequently underwent autologous SCT and the two patients with strongyloidiasis diagnosed during the neutropenic phase of SCT developed a syndrome of hyperinfection or disseminated strongyloidiasis. 3,4 After having completed these studies, we concluded that, given the low incidence of complications and the endemic character of strongyloidiasis in Brazil, no routine screening or prophylaxis would be performed. Patients who develop complications during transplant that may be attributed to a complication of strongyloidiasis are screened with multiple stool examinations and pre-emptively treated.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…5 None of our patients enrolled in the prospective study, including those who subsequently underwent autologous SCT and the two patients with strongyloidiasis diagnosed during the neutropenic phase of SCT developed a syndrome of hyperinfection or disseminated strongyloidiasis. 3,4 After having completed these studies, we concluded that, given the low incidence of complications and the endemic character of strongyloidiasis in Brazil, no routine screening or prophylaxis would be performed. Patients who develop complications during transplant that may be attributed to a complication of strongyloidiasis are screened with multiple stool examinations and pre-emptively treated.…”
mentioning
confidence: 99%
“…In our study, an ELISA test had sensitivity, specificity, positive and negative predictive values of 68, 89, 48 and 95%, respectively. 3 Another possibility would be to give prophylaxis to all patients from endemic areas. We tested this strategy in a double-blind randomized study comparing thiabendazole and placebo given once every month, and did not find a benefit of giving thiabendazole, with similar incidences of strongyloidiasis and fewer side effects in the placebo group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…La ricerca di anticorpi anti-S. stercoralis è stata eseguita con il metodo ELISA S. ratti (Bordier Affinity Products, CH, distribuito da Effegiemme srl, Milano), dotato di sensibilità e specificità dichiarate rispettivamente dell'88 e del 95% (7,9). Il kit era costituito da 96 pozzetti sensibilizzati con antigeni larvali somatici di S. ratti.…”
Section: Materiali E Metodiunclassified
“…Fardet y cols., observaron una mayor frecuencia de parasitados por Strongyloides stercoralis en individuos alcohólicos, diabéticos, portadores del virus linfotrópico humano de células T del tipo 1 (HTLV-1), pacientes receptores de trasplantes o en corticoterapia 13 . Otros estudios realizados identificaron la ocurrencia de estrongiloidiasis en pacientes infectados por el virus de la inmunodeficiencia humana (VIH) y con neoplasias hematológicas, con prevalencias que variaban entre 5,5 a 12,0% 14,15 y 8,3 a 23% 16,17 , respectivamente.…”
unclassified